2016
DOI: 10.1097/mat.0000000000000383
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Concomitant Procedures with Left Ventricular Assist Device Implantation: Implications by Device Type and Indication

Abstract: Guidelines for performing concomitant procedures (CPs) in patients undergoing continuous flow-left ventricular assist device (CF-LVAD) implantation are unclear. The impact of an increased surgical complexity outside the constraint of landmark clinical trials has not been reported. From May 2004 to December 2013, 614 patients (499 males, 81%) underwent CF-LVAD implant at our institutions. Median age was 57 ± 13 years and 364 (59%) were bridge to transplantation (BTT). Survival and device-related complications w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…Morgan et al demonstrated that concomitant cardiac procedures like aortic or tricuspid valve surgery during LVAD implantation are not assumed with higher procedural risks [ 2 ]. Maltais et al reported about similar findings but emphasized the patient-to-patient-wise decision-making with focus on age, preoperative renal function, and the complexity of planned surgery [ 3 ].…”
Section: Discussionmentioning
confidence: 90%
“…Morgan et al demonstrated that concomitant cardiac procedures like aortic or tricuspid valve surgery during LVAD implantation are not assumed with higher procedural risks [ 2 ]. Maltais et al reported about similar findings but emphasized the patient-to-patient-wise decision-making with focus on age, preoperative renal function, and the complexity of planned surgery [ 3 ].…”
Section: Discussionmentioning
confidence: 90%
“…However, donor heart sources are limited, and the donor heart should be given to those recipients with a relatively small risk to achieve maximum benefit (3). Whether a recipient for HTx with a prior cardiac surgery history is at greater risk than someone without prior cardiac surgery is still under discussion, and there is no clear consensus (4)(5)(6). Moreover, the widely used bicaval anastomosis method in HTx still has some postoperative complications such as left atrial thrombosis and anastomotic hemorrhage (7), which is why we propose a novel fourcorner traction bicaval anastomosis combined with a continuous everting suture technique.…”
Section: Introductionmentioning
confidence: 99%
“…Coexisting concomitant cardiac disease addressed surgically might complicate the placement and efficient functioning of left ventricular assist devices (LVADs) [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%